MRI evaluation of asymmetry of nigrostriatal damage in the early stage of early-onset Parkinson's disease. Issue 6 (June 2015) - Wang, Jianli; Yang, Qing X.; Sun, Xiaoyu; Vesek, Jeffrey; Mosher, Zachary; Vasavada, Megha; Chu, Jonathan; Kanekar, Sangam; Shivkumar, Vikram; Venkiteswaran, Kala; Subramanian, Thyagarajan
Abstract: Introduction: The motor symptoms and signs of early-onset idiopathic Parkinson's disease (PD) in Hoehn and Yahr (H&Y) stage-1 are generally unilateral. We hypothesized that there would be detectable differences in the quantitative MRI parameters in these PD patients between the hemispheres contralateral to the clinically symptomatic and non-symptomatic body side. Methods: We tested this hypothesis by comparing transverse relaxation rates and diffusion tensor imaging (DTI) parameters in the substantia nigra and putamen between the two hemispheres contralateral to the symptomatic and non-symptomatic side in H&Y stage-1 PD patients who had onset of symptoms between ages of 40–59 years. Results: There were quantifiable hemispheric asymmetries in transverse relaxation rates in the substantia nigra, as well as fractional anisotropy and mean diffusivity in the putamen in early PD, which correlated with the unilaterality of motor symptoms as evaluated using the motor portion of the Unified Parkinson's Disease Rating Scale. Conclusion: Transverse relaxation mapping and DTI demonstrated significant differences between the symptomatic and non-symptomatic hemispheres at the early stage of early-onset PD. These findings support the hypothesis of asymmetric neurodegeneration in the bilateral nigrostriatal pathways in the early stage of the disease. Highlights: Hemispheric differences in early stage Parkinson's disease were studied using MRI. Hemispheric asymmetry exists in transverse relaxation rates in the substantia nigra. Hemispheric asymmetry exists in diffusion parameters in the putamen. Nigrostriatal neurodegeneration can be asymmetric in early stage Parkinson's disease.